DNA binding properties of the Escherichia coli nitric oxide sensor NorR: towards an understanding of the regulation of flavorubredoxin expression. (1st February 2005) - Tucker, N.; D'Autréaux, B.; Spiro, S.; Dixon, R.
Abstract : Nitric oxide is an intermediate of denitrification, and is one of the radical species deployed by macrophages against invading pathogens, therefore bacterial responses to NO are of considerable importance. The Escherichia coli flavorubredoxin and its associated oxidoreductase reduce NO to nitrous oxide under anaerobic conditions, and are encoded by the norVW transcription unit. Expression of norVW requires the NO sensing regulatory protein NorR and is dependent on RNA polymerase containing the alternative sigma factor, σ 54 . We have purified NorR and shown that it binds to three sites in the norVW promoter region, located 75–140 bp upstream of the experimentally verified transcription start site. We have also identified two binding sites for the integration host factor, one between the NorR sites and the σ 54 -RNA polymerase binding site, and a second downstream of the norVW transcription start site. Comparison of the norVW promoters of enteric bacteria along with known and putative NorR-regulated promoters from Vibrio, Ralstonia and Pseudomonas species suggests that NorR binding sites contain an invariant GT(N7)AC motif flanking an AT-rich central region. The identification of a consensus for NorR binding sites will help to elucidate additional members of the NorR regulon.